New insights into the use of Neolithic pottery in Guangxi of South China: organic residue analysis of experimental and archaeological pottery - Xiaodi Liu; Meng Ren; Yongxu Fu; Yaowu Hu; Shuzhi Wang; Yimin Yang (Heritage Science, 2023)
Abstract As one of the world’s earliest pottery origins in Eurasia, the role of pottery during Neolithic period in South China remains unclear. Here, we present a new understanding on the utilization pattern of early pottery from the Neolithic sites of Dayan, Dingsishan and Zengpiyan in Guangxi province, China. Compound-specific stable isotope analysis of pottery and bone lipids show that a persistent use of terrestrial C3 and C4 resources throughout the pottery utilization history highlight the culinary practice and terrestrial exploitation during Neolithic period. Contrary to the traditional view that the primary use of these pottery was closely linked with aquatic resource processing, no aquatic biomarkers were found in the potsherds, yet these compounds were detected in the cooking experiments in this study, indicating that aquatic resources in these sites were probably processed or consumed in other ways. Moreover, a remarkable diachronic change from extensive use of C3 and C4 resources to the intensive use of certain kinds of C3 resources in different Neolithic stages, further indicating that an ecological tradition rooted in the subtropical and tropical environments as well as the Neolithic social evolution exerted great influence upon the initial production and the subsequent utilization of early pottery in prehistoric South China.